THE ROLE OF ALCOHOL INVOLVEMENT IN MAXILLOFACIAL TRAUMA. - Elitsa Deliverska; Liudmil Gagov; Martin Rubiev (Journal of IMAB, 2012)
Introduction: Alcohol is regularly consumed by individuals in social settings. However, overindulgence can lead to impaired judgment and physical harm. Patients who have sustained alcohol - related injuries are frequently treated in departments of Oral and Maxillofacial surgery. This study exams the association between alcohol consumption and maxillofacial trauma treated at the Department of Maxillofacial surgery - 'St. Anna' Hospital in Sofia for 5 years period. Materials and methods: A minimum dataset was collected prospectively by maxillofacial staff after the first examination of an emergency referral. Information was entered on to a designed database and analysed for a 5-year period. Different data for the victims including age, sex, ethnic group, social status, type of fractures, mode of injury, and treatment delivered was gathered and analyzed. Results: A total of 94 patients were identified to have alcohol-related injuries. More than 4/5 were male of which almost 70% are between 17 and 50 years old. Assault was the most often cause of trauma, followed by motor vehicle accident and fall as third reason for injuries. Other etiologies differ and were presented by fewer cases.Conclusion: The maxillofacial region is by far the most frequently selected target in assault in adults. There is a casual link between alcohol intoxication and injury. Alcohol-related injuries continued to be the main problem in young male adults involved in fights. Significant problem are road accidents caused by alcohol-influenced drivers. Therefore we believe that there should be public awareness to educate these people for the harmful effect of drinking.